USM AMONG TOP FIVE GREEN SUSTAINABLE UNIVERSITIES IN MALAYSIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
SERDANG, 25 May 2017 Universiti Sains Malaysia (USM) along with 4 other Malaysian public universities (UA) have been chosen to receive the Green Campus Sustainability Award 2017 in conjunction with the Green Campus Sustainability Convention 2017 held at Universiti Putra Malaysia (UPM).